COMPOSITE METAL ALLOY-BASED CUTTING TOOL FOR HÖRLLER INDUSTRIAL PAPER CUTTING - Lima da Silva, Isomar; Ribeiro Brazão, Jessica; Stefani Modenezi, Matheus; Costa dos Santos, Rodrigo (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
The Hörller industrial paper cutting requires tools of high precision and durability to meet the needs of the printing and packaging industry. This article covers the development of an innovative cutting tool based on a composite metal alloy, designed to address the specific challenges of this process. The main objective of this study is to design and manufacture a cutting tool that is able to meet the demands of industrial paper cutting type Hörller, providing high efficiency, quality and extended service life. The development process of the cutting tool involved the precise definition of the geometry, the careful selection of the composite alloy material, the application of heat treatment and specialized sharpening techniques. Detailed tests were conducted to evaluate the tool’s performance under industrial conditions. The results demonstrate that the cutting tool based on the composite metal alloy provides a remarkable efficiency in the cutting of Hörller-type paper, significantly surpassing conventional alternatives. In addition, its durability has been proven in long periods of industrial operation, minimizing the need for maintenance. This study contributes to the advancement of industrial cutting tool technology, offering a robust and effective solution for Hörller-type paper cutting. The developed tool represents a milestone in the optimization of the cutting process, promoting greater productivity and quality in the printing and packaging industry.